Figure 8 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 8. Strombidium apolatum nov. spec. from life (A–C) and after protargol impregnation (D–I). (A) Ventral view of a typical specimen; (B) to show a cell attached to the bottom; (C) pattern of movement; (D) dorsal view, to show the arrangement of extrusomes (arrows); (E) ventral–lateral view, to show the girdle and ventral kinety, which almost meet at equatorial area (arrow and arrowhead, respectively); (F) anterior portion of ventral view, to show the buccal structure: arrow marks the paroral membrane, double-arrowheads indicate the buccal membranelles, arrowheads point to the collar membranelles; note the highly developed cytopharyngeal fibres extending backwards; (G) ventral view, arrow marks the subpellicular platelet layer; (H) dorsal view, arrow marks the equatorial girdle, arrowhead points to the gap between girdle and ventral kinety; (I) an individual in early divisional stage, double-arrowheads mark the newly formed collar membranelles, while arrow indicates the buccal ones; note the paroral membrane (arrowhead). Scale bar: 30 Mm. : Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 954, DOI: 10.1080/00222930400001509, http://zenodo.org/record/4657793